Penyetaraan Tes UAN: MAengapa dan Bagaimana? - Sukirno Sukirno (LPMPP Universitas Negeri Yogyakarta, 2007)
Debates concerning what is right and what is wrong with national final examination (UAN) in Indonesia are not new. National final examination (UAN), a significant process using a test form to measure learning output, has been developed to provide useful information for the decision makers (parents, educators, policy-makers and the local community). Multiple forms of a certification exam are desirable for a variety of reasons. However, the problem of comparability among test scores using different test forms must be addressed in order to insure fairness and consistency in each testing situation. Test forms must be interchangeable across test administrations. Psychometric procedures known as equating methods can be utilized to produce comparable (equated) scores. Equating procedures consist of (1) a design for collecting test data for equating, (2) a clearly defined level of expected correspondence among test scores, and (3) specific statistical procedures that are used to estimate score correspondence. The process of equating is used to obtain comparable scores when more than one test forms are used in a test administration. In many situations in test administration, more than one form of the tests are used for security reasons. Beside, by test equating, a test form can be administered more flexible in the context of environment and time. There are several techniques and methodologies that can be used in equating test forms. Generally speaking, these techniques and methodologies can be divided into three major activities, namely determining test equating design, determining the test equating methods, and determining the way of test equating will be taken. The magnitude of standard error of estimate (SEE) is used to evaluate which is the most accurate method of test equating. The less the score of standard error of estimate the more accurate of the test equating method.